LEARNING DESIGN WITH DISCOVERY LEARNING MODEL FOR MATEMATICAL COMPUTATIONAL THINKING ABILITY - Aulia Kartika Syari; Tian Abdul Aziz (Universitas Muhammadiyah Lampung, 2025)
Designing instruction in a structured manner is essential to ensure that the learning process is effective, focused, and aligned with the needs of the learners.. This article aims to develop a learning design on the topic of SPLDV to improve computational thinking skills in junior high school students in East Jakarta City. This research is part of the instructional design of the ADDIE model which consists of Analysis, Design, Development, Implementation, and Evaluation. Based on the ADDIE development model, this research is limited to the design stage. The previous steps were developed through an instructional design that carried out a needs analysis in which classroom observations and needs interviews were conducted. The needs analysis was conducted on a class VIII in a junior high school in East Jakarta City with a total of 30 participants. Apart from the needs analysis to the learners, an interview was also conducted with one mathematics teacher at the school. Through the process of analyzing the needs obtained, a learning design has been formed and will be applied to further learning. The results of the discussion have been obtained to improve the process of computational thinking ability on SPLDV material can use the discovery learning model.